2022
DOI: 10.3390/ani12070870
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Probiotic Bacillus subtilis on Injurious Behavior in Laying Hens

Abstract: Intestinal microbiota functions such as an endocrine organ to regulate host physiological homeostasis and behavioral exhibition in stress responses via regulating the gut–brain axis in humans and other mammals. In humans, stress-induced dysbiosis of the gut microbiota leads to intestinal permeability, subsequently affecting the clinical course of neuropsychiatric disorders, increasing the frequency of aggression and related violent behaviors. Probiotics, as direct-fed microorganism, have been used as dietary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 223 publications
(296 reference statements)
0
7
0
5
Order By: Relevance
“…It has a wide range of species, which are typically classified as Lactobacillus , Bifidobacterium and Gram-positive cocci, and yeast ( Saccharomyces ) genera ( Fijian, 2014 ), with health benefits, growth promotion, non-toxic side effects, and other characteristics. Probiotics supplementation in laying hen diets have been proven to improve hen’s performance parameters including egg production, feed conversion ratio and egg quality, disease resistance and animal welfare ( Smith, 2014 ; Villageliu and Lyte, 2017 ; Khan et al, 2020 ; Sjofjan et al, 2021 ; Bindari and Gerber, 2022 ; Jiang et al, 2022 ). For instance, Macit et al (2021) reported that supplementation of humate and probiotics into diets could improve the content of monounsaturated fatty acids in yolk, feed conversion ratio and yolk color.…”
Section: Introductionmentioning
confidence: 99%
“…It has a wide range of species, which are typically classified as Lactobacillus , Bifidobacterium and Gram-positive cocci, and yeast ( Saccharomyces ) genera ( Fijian, 2014 ), with health benefits, growth promotion, non-toxic side effects, and other characteristics. Probiotics supplementation in laying hen diets have been proven to improve hen’s performance parameters including egg production, feed conversion ratio and egg quality, disease resistance and animal welfare ( Smith, 2014 ; Villageliu and Lyte, 2017 ; Khan et al, 2020 ; Sjofjan et al, 2021 ; Bindari and Gerber, 2022 ; Jiang et al, 2022 ). For instance, Macit et al (2021) reported that supplementation of humate and probiotics into diets could improve the content of monounsaturated fatty acids in yolk, feed conversion ratio and yolk color.…”
Section: Introductionmentioning
confidence: 99%
“…Sabendo que as aves sob condições comerciais criadas em gaiolas ou em alta densidade podem apresentar comportamento anormal, como agressividade, bicagem e até canibalismo, resultante de estresse (Hedlund & Jensen, 2022;Jiang et al, 2022), a manutenção do equilíbrio da microbiota é crucial para a homeostase fisiológica e comportamental, saúde, bem-estar (Jiang et al, 2022) e qualidade dos ovos produzidos (Hedlund & Jensen, 2022). Assim, a suplementação com probióticos torna-se uma ótima opção, pois promove efeitos benéficos à saúde em resposta ao estresse das aves, além de melhorar o processo de adaptação ao ambiente de produção (Jha et al, 2020;Krysiak et al, 2021).…”
Section: Resultsunclassified
“…Vários mecanismos de ação dos probióticos à base de bacillus spp. foram propostos, dentre eles a viabilização da atividade neuroquímica (Jiang et al, 2022), por meio da manutenção da microbiota equilibrada, resultando em melhor saúde e integridade intestinal. Esta ação facilita a síntese e secreção de neurotransmissores como a serotonina, estimulando o eixo intestino-cérebro (Jiang et al, 2022;Lyte et al, 2022;Cheng et al, 2001;Cheng et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Dietary supplementation with Enterococcus faecium AL41 increased the number of myonuclei per fiber, improved capillarization, and further improved body weight owing to the high intramuscular expression of IGF-1 and lowered MYF5 expression in broilers ( Albrecht et al , 2022 ). In addition, microbiota dysbiosis may induce neuroinflammation via the microbiota–gut–brain axis, which causes injurious behaviors in chickens ( Jiang et al , 2022 ; Shamshirgaran et al , 2022 ). Jiang et al (2022) showed that the probiotic B. subtilis reduced stress-induced injurious behavior by mediating the gut–microbiota–brain axis.…”
Section: Beneficial Properties and Applications Of Probiotics In Chic...mentioning
confidence: 99%